ETV5 transcription factor is upregulated in ovarian cancer and contributes to ovarian tumor progression and dissemination - Llaurado, Marta (2011)
Epithelial ovarian cancer is the most lethal gynecological malignancy and the fifth leading cause of cancer deaths in women in the Western world. ETS transcription factors are known to act as positive or negative regulators of the expression of genes that are involved in various biological processes, including those that control cellular proliferation, differentiation, apoptosis, tissue remodeling, angiogenesis and transformation. ETV5 belongs to the PEA3 subfamily. PEA3 subfamily members are able to activate the transcription of proteases, matrix metalloproteinases and tissue inhibitor of metalloproteases, which is central to both tumor invasion and angiogenesis. Here, we examined the role of the ETV5 transcription factor in epithelial ovarian cancer and we found ETV5 was upregulated in ovarian tumor samples compared to ovarian tissue controls. The in vitro inhibition of ETV5 decreased cell proliferation in serum-deprived conditions, induced EMT and cell migration and decreased cell adhesion to extracellular matrix components. ETV5 inhibition also decreased cell–cell adhesion and induced apoptosis in anchorage-independent conditions. Accordingly, upregulation of ETV5 induced the expression of cell adhesion molecules and enhanced cell survival in a spheroid model. Our findings suggest that the overexpression of ETV5 detected in ovarian cancer cells may contribute to ovarian tumor progression through the ability of ETV5 to enhance proliferation of ovarian cancer cells. In addition, upregulation of ETV5 would play a role in ovarian cancer cell dissemination and metastasis into the peritoneal cavity by protecting ovarian cancer cells from apoptosis and by increasing the adhesion of ovarian cancer cells to the peritoneal wall through the regulation of cell adhesion molecules.